Crystallization kinetics and heat treatment temperature on microstructure and properties of Na2O-CaO-P2O5 bioactive glass system - Pratthana Intawin (2018)
© 2018 This study deals with the effects of heat treatment temperature on the thermal and mechanical properties of Na2O-CaO-P2O5 glasses and glass-ceramics. The major crystalline phase was calcium phosphate along with sodium calcium phosphate as the minor crystalline phases presented in the glass-ceramics. Vickers hardness, Knoop hardness and Young's modulus values of the glass-ceramics decrease with increasing of heat treatment temperature, however, the opposite trend is found for the fracture toughness values. H550 sample confirms the dendritic-like structure, H600 and H650 samples confirms the lamellar bone-like structures and H700 sample confirms the scaffold-like structure. The microstructure, with cluster of dendritic crystal and lamellar structure, indicates a typical two-dimensional crystallization mechanism, which agrees with the above analysis of Avrami exponent (n = 2.8) for glass sample at Tp1 while scaffold structure indicates a typical three-dimensional crystallization mechanism, which is in good agreement with the above analysis of Avrami exponent (n = 4.2) for glass sample at Tp2. Moreover, all Na2O-CaO-P2O5 bioactive glass-ceramics are not toxic to the living cell and have a good bioactive property.